Nitrous Oxide Emission from an Upland Cropping System in the Humid Tropics - Khalil, Mohammad Ibrahim (2001)
Nitrous oxide (N20) emission to the atmosphere has a great implication on global climate change. Agricultural soils seem to be its major source, though little attention is given to the soils and upland cropping systems of the humid tropics. Thus, laboratory experiments were carried out to study the impact of N sources, moisture regimes and soil types on N20 production A field experiment was conducted to measure N20 emissions from a maize-groundnut cropping system managed with different N sources. The laboratory incubation study using an Ultisol showed a maximum N20 flux of 2379 ug N20-N kg-1 soil d-1 with chicken manure application at 60010 water-filled pore space (WFPS). Application of potassium nitrate, groundnut residue and urea resulted in smaller production rates (61 5 - 699 ug N20-N kg-l soil d-1). Addition of ammonium sulfate and maize residue produced the lowest rates, 229 and 246 ug N20-N kg-1 soil d-1, respectively. In general, the total N20 production in 25 days increased with decrease in C/N ratio of the organic N sources.